Analysis of 50/70 foamed bitumen properties in the aspect of its utilization in mineral-bitumen mixtures - Chomicz-Kowalska, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The aim of the study was to analyze the properties of foamed bitumen produced from 50/70 bitumen in terms of the assessment of its usefulness to the road construction materials. In order to improve the foaming parameters the synthetic wax Fischer-Tropsch (FT) in an amount of 1.0%, 2.0% and 3.0% was used. Bitumen binder parameters were evaluated before and after the foaming process. The basic parameters were evaluated (before the foaming process): penetration, Fraass breaking point and softening point. The bitumen foam parameters were measured at the foaming water content (FWC) in the range from 1.5% to 4.0% with an increment of 0.5%. The tests allowed determining optimal application ranges for the FT and the FWC to produce asphalt at lower temperatures.